Innovation of Topical Metformin as Anti-Inflammatory Effects in Hemorrhoid Rat Model: Literatur Review - Ummi Chairunnisa; Darmawi Darmawi; Benni Iskandar (PSPP JOURNALS, 2026)
Hemorrhoids are a common anorectal disorder characterized by vascular dilation, tissue edema, and inflammation mediated by cytokines such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and cyclooxygenase-2 (COX-2). Current therapies mainly relieve symptoms without adequately targeting the underlying inflammatory process. Metformin, widely used as an antidiabetic drug, has demonstrated anti-inflammatory properties through activation of the adenosine monophosphate-activated protein kinase (AMPK) pathway and inhibition of nuclear factor kappa B (NF-κB). Topical administration may enhance local therapeutic effects while minimizing systemic exposure. This literature review aimed to evaluate the potential of topical metformin as an innovative treatment for hemorrhoids and to examine its anti-inflammatory effects in rat hemorrhoid models. Relevant studies were identified from PubMed, Scopus, ScienceDirect, and Google Scholar using predefined keywords related to topical metformin, inflammation, hemorrhoids, AMPK, and COX-2. Eligible full-text articles were narratively synthesized to evaluate mechanisms of action, therapeutic efficacy, and formulation strategies. The reviewed evidence indicates that metformin suppresses inflammatory responses by activating AMPK, inhibiting NF-κB signaling, and reducing TNF-α, IL-6, and COX-2 expression. Animal studies consistently reported reduced inflammatory cell infiltration, decreased edema, improved tissue architecture, and enhanced local drug retention with topical formulations. Overall, topical metformin represents a promising therapeutic strategy for hemorrhoids by targeting inflammation and promoting tissue repair. Nevertheless, further experimental studies and well-designed clinical trials are necessary to establish its safety, efficacy, and optimal formulation for clinical use.